Berlin Ewa Szwagrzyl. - Omilanowska, Małgorzata; Szwagrzyl, Ewa (London Dorling Kindersley, 2000)
A guide to Berlin which covers all the major sights, museums, historic and modern buildings, parks and forests. Cutaways, floor plans and 3-D maps help the reader to explore sights including the Peramon Museum and Schloss Charlottenburg. Information is also given for hotels and restaurants.
Include index.
Keywords: Berlin (Germany) -- Guidebooks; Berlin (Germany) -- Description and travel